FAKTOR-FAKTOR YANG MEMPENGARUHI PENYESUAIAN KARIR PEGAWAI (Studi Pada ASN Organisasi Publik di Kota Banjarmasin) - Rahmi Widiyanti; Basuki Basuki; Mursanto Mursanto (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2022)
Organizations are always changing with shifting in leadership. Employees are required to be able to adapt to changes in the organization, including the existence of work shifting in the organization. Employees are required to have professionalism in their work in order to provide good service to the user community. At this point, the employee's personality traits and career adaptability are very important. Relevant research shows that the ability to adapt to a career should not be overlooked when career planning is made. This study examines the relationship between employee personality traits and career adjustment abilities, who work in the public sector in the Banjarmasin City (n = 100). Using the survey method, data was collected from village officials. According to the results of data analysis, five personality factors and identification dimensions, and each dimension are grouped into three levels. Factor analysis was applied to the expression of career adaptability, with four factors. The results showed that there were significant differences in employee’s career adjustments according to the personality traits of each employee’s.